Three new species of Trichoderma in the Harzianum and Longibrachiatum lineages from Peruvian cacao crop soils based on an integrative approach - Bustamante D.E. (2021)
This study was supported by National Institute of Agricultural Innovation (INIA) grant 004-2016-INIA-PNIA-UPMSI/IE through the National Program for Agricultural Innovation of Peru (PNIA), by grant 10-2018-FONDECYT-BM-ADT-AV from National Foundation for Scientific, Technological Development and Technological Innovation (Fondecyt) of Peru, and by grant SNIP no. 352641?CEINCACAO.